Improving Delivery of Secondary Prophylaxis for Rheumatic Heart Disease in a High‐Burden Setting: Outcome of a Stepped‐Wedge, Community, Randomized Trial. Issue 14 (17th July 2018) - Ralph, Anna P.; de Dassel, Jessica L.; Kirby, Adrienne; Read, Clancy; Mitchell, Alison G.; Maguire, Graeme P.; Currie, Bart J.; Bailie, Ross S.; Johnston, Vanessa; Carapetis, Jonathan R.
Abstract : Background: Health system strengthening is needed to improve delivery of secondary prophylaxis against rheumatic heart disease. Methods and Results: We undertook a stepped‐wedge, randomized trial in northern Australia. Five pairs of Indigenous community clinics entered the study at 3‐month steps. Study phases comprised a 12 month baseline phase, 3 month transition phase, 12 month intensive phase and a 3‐ to 12‐month maintenance phase. Clinics received a multicomponent intervention supporting activities to improve penicillin delivery, aligned with the chronic care model, with continuous quality‐improvement feedback on adherence. The primary outcome was the proportion receiving ≥80% of scheduled penicillin injections. Secondary outcomes included "days at risk" of acute rheumatic fever recurrence related to late penicillin and acute rheumatic fever recurrence rates. Overall, 304 patients requiring prophylaxis were eligible. The proportion receiving ≥80% of scheduled injections during baseline was 141 of 304 (46%)—higher than anticipated. No effect attributable to the study was evident: in the intensive phase, 126 of 304 (41%) received ≥80% of scheduled injections (odds ratio compared with baseline: 0.78; 95% confidence interval, 0.54–1.11). There was modest improvement in the maintenance phase among high‐adhering patients (43% received ≥90% of injections versus 30% [baseline] and 28% [intensive], P <0.001). Also, the proportion of days at risk in the whole cohort decreased in the maintenance phase (0.28 versus 0.32 [baseline] and 0.34 [intensive], P =0.001). Acute rheumatic fever recurrence rates did not differ between study sites during the intensive phase and the whole jurisdiction (3.0 versus 3.5 recurrences per 100 patient‐years, P =0.65). Conclusions: This strategy did not improve adherence to rheumatic heart disease secondary prophylaxis within the study time frame. Longer term primary care strengthening strategies are needed. Clinical Trial Registration: URL: www.anzctr.org.au . Unique identifier: ACTRN12613000223730.